Molecular insights into nucleocapsid assembly and transport in Marburg and Ebola viruses - Takamatsu, Yuki; Dolnik, Olga; Hirabayashi, Ai; Okamoto, Kenta; Kurashige, Tomomi; Shangfan, Hu; Oda Harumi, Catarina; Noda, Takeshi (mBio, 2025)
This study provides crucial insights into the molecular mechanisms of nucleocapsid assembly and transport in filoviruses, specifically Marburg virus (MARV) and Ebola virus (EBOV). Using advanced live-cell imaging, we uncovered how the conserved PPxPxY motif in nucleoprotein (NP) mediates its interactions with VP30, thereby regulating nucleocapsid formation and viral replication. Notably, while VP30’s role differs between MARV and EBOV, the underlying mechanism of NP-VP30 interaction via this motif appears conserved across filoviruses, making it a promising target for broad-spectrum antiviral strategies. These findings deepen our understanding of nucleocapsid protein compatibility and virus-host interactions, offering new avenues for therapeutic intervention against these deadly pathogens.